STUDI KERUSAKAN PRASARANA JALAN DI PASAR SENTRAL KALIBOBO KABUPATEN NABIRE TERHADAP AKTIVITAS EKONOMI MASYARAKAT - Semuel Rorroong D (JURNAL TEKNIK SIPIL CENDEKIA (JTSC), 2022)
Damage to roads will cause many losses to community activities or activities, especially economic activities that can be felt by users directly and also economic actors, in this case local market traders.Similar problems can be seen in road conditions in Kalibobo Central Market, Nabire Regency, Province Papua, in almost the last one period, the road at Kalibobo Central Market, Nabire Regency, is very concerned about. Many people have complained to the local Regency Government to pay attention to this road but until now it has not been well realized. The objectives of this study are: "Knowing the effects of damage to road infrastructure at the Kalibobo Central Market on the Economic Activities of the Nabire Regency Community." The data analysis method used by the writer is descriptive qualitative with data collection techniques used, namely observation and interviews, the results obtained are the effect of road damage on economic activity, among others: Inadequate road class, vehicle intensity with large loads, parking area that is not regular, Lack of Government Attention. Therefore it is necessary to have a thorough road paving by the Nabire Regency government so that economic activity in the Kalibobo central market can work well.